2011
DOI: 10.1177/1358863x10392474
|View full text |Cite
|
Sign up to set email alerts
|

Emerging diagnostic and therapeutic molecular imaging applications in vascular disease

Abstract: Assessment of vascular disease has evolved from mere indirect and direct measurements of luminal stenosis to sophisticated imaging methods to depict millimeter structural changes of the vasculature. In the near future, the emergence of multimodal molecular imaging strategies may enable robust therapeutic and diagnostic (‘theragnostic’) approaches to vascular diseases that comprehensively consider structural, functional, biological and genomic characteristics of the disease in individualized risk assessment, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…A review of nanoparticles for imaging of atherosclerosis can be found elsewhere . Theranostic nanoparticles with dual therapeutic and diagnostic functionality are reviewed by Eraso et al and Tang et al Additional insight regarding formulations of nanoparticles and their in vivo behavior can be found in other reviews . A summary of challenges, clinical barriers, and a future outlook of nanomedicine in atherosclerosis are also discussed herein.…”
Section: Nanomedicinementioning
confidence: 99%
“…A review of nanoparticles for imaging of atherosclerosis can be found elsewhere . Theranostic nanoparticles with dual therapeutic and diagnostic functionality are reviewed by Eraso et al and Tang et al Additional insight regarding formulations of nanoparticles and their in vivo behavior can be found in other reviews . A summary of challenges, clinical barriers, and a future outlook of nanomedicine in atherosclerosis are also discussed herein.…”
Section: Nanomedicinementioning
confidence: 99%
“…Atherosclerosis is the basic pathological character underlying most vascular events. The degree of endothelial dysfunction, inflammatory activity, atherosclerotic stenosis, platelet agreeability and neovascularization are important factors affecting the progression of atherosclerosis [2]. Current combinational therapies for vascular disease mainly focus on modification of lifestyle, management of risk factors and interventional treatments [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…[21] In theranostics, drug delivery and subsequent action in a region of interest is controlled by an external energy field – mostly ultrasound, light, or a magnetic field – in an attempt to minimise systemic and local effects. [22]…”
Section: Theranosticsmentioning
confidence: 99%